A Wireless Collision Detection on Transmission Poles through IoT Technology - Dhaya, R.; Kanthavel, R. (Journal of Trends in Computer Science and Smart Technology, 2020)
Transmission poles plays a major in the wired telecom communication as well as in the electrical transmission. The wireless communication receivers and antennas are also need poles for holding the antenna and several other peripheral units to its nearby. Most of the transmission poles are kept on the public places for providing a better communication signal and the electric supply. The road side transmission poles are extremely not protected with any safety devices. Those poles are standing on its own strength on the materials used for making the poles. Due to aging and several other factors there are chances for such poles to get damage very easily. Vehicle collision is an important factor in damaging the transmission poles kept near the road side. The proposed method is designed to identify the collision detection on the poles to alert the maintenance team to take immediate action against the faulty poles. It is achieved with the help of IoT technology connecting several peripheral units to a microcontroller.